2017
DOI: 10.1186/s13012-017-0590-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of electronic audit and feedback: intervention effectiveness and use of behaviour change theory

Abstract: BackgroundAudit and feedback is a common intervention for supporting clinical behaviour change. Increasingly, health data are available in electronic format. Yet, little is known regarding if and how electronic audit and feedback (e-A&F) improves quality of care in practice.ObjectiveThe study aimed to assess the effectiveness of e-A&F interventions in a primary care and hospital context and to identify theoretical mechanisms of behaviour change underlying these interventions.MethodsIn August 2016, we searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 47 publications
3
117
0
Order By: Relevance
“…[ 31 33 ] A recent systematic review of electronic audit and feedback interventions suggested that insufficient clarity in previous studies meant the active components of interventions could not be fully understood, and recommended that future evaluations of systems should utilise theoretical approaches. [ 34 ] This study specifically aimed to explore the ways in which the intervention was implemented, adopted and embedded into everyday practice (or not) using a qualitative process evaluation consisting of semi-structured interviews with pharmacists, general practitioners, and other general practice staff.…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 33 ] A recent systematic review of electronic audit and feedback interventions suggested that insufficient clarity in previous studies meant the active components of interventions could not be fully understood, and recommended that future evaluations of systems should utilise theoretical approaches. [ 34 ] This study specifically aimed to explore the ways in which the intervention was implemented, adopted and embedded into everyday practice (or not) using a qualitative process evaluation consisting of semi-structured interviews with pharmacists, general practitioners, and other general practice staff.…”
Section: Introductionmentioning
confidence: 99%
“…The work to date [5][6][7]12] reinforces the role of a bottom-up approach targeting stakeholder engagement, ERAS as the standard approach, the role of education and training, the opportunity to involve patients [14], the importance of audit and feedback [22] visibility of the initiative and the role of nurse coordinators and champions. In order to drive health system transformation we can build upon drivers of High-performance learning systems that engage at the front lines combined with the role of leaders in top-down management strategies that focus on system metrics, process and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that the visual display of performance in feedback interventions can significantly moderate its effects on clinical practice [3,4]. Therefore, important mechanisms of action for A&F may be related to the use of visualizations [5][6][7]. We understand visualizations to include charts, tables, and hybrid displays of graphical elements in tables [8], all of which are commonly used in feedback reports and clinical quality dashboards [9,10].…”
Section: Introductionmentioning
confidence: 99%